(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
Extracts of many higher plants have been reported to exhibit antifungal properties under Laboratory experiment. This study was therefore carried out to investigate the effect of Carica papaya plant extracts on seed borne pathogen of African yam bean. Seed health test of African yam bean was carried out using blotter paper method. Test of plant extract for inhibition of radial growth of seed borne pathogen of African yam bean was studied under in-vitro experiment at 0%, 50%, 75% and 100% concentrations with 0% as the control. The design used was a completely randomized design (CRD) with three replications. The test plant extracts of different concentrations were added into petri dishes containing molten sterilized Sabouraud Dextrose Agar (SDA) and swayed gently on the Laboratory bench to allow even mixing. These were allowed to gel. Then nine-millimeter discs of a seven-day pure culture of Aspergillus flavus were aseptically placed on the center of the petri dishes containing the SDA-extract mixture. Record on radial inhibition effect of the test plant extract was kept for further analysis. Analysis of variance (ANOVA) was conducted on data on radial inhibition of test fungus. Results showed that Aspergillus niger, Aspergillus flavus and Aspergillus terreus were isolated from incubated African yam bean seeds. Results also showed that Carica papaya leaf extract used was very effective and the higher the concentrations of extract, the more effective in the inhibition of radial growth of the test fungal organism. It could therefore be recommended that farmers should always conduct viability test on procured seeds for planting. That farmers should rather use plant extract such as was used in this investigation if stabilized in controlling seed borne fungal pathogens of African yam bean seeds than synthetic fungicides.